Hatching and growth performances of guinea fowl under intensive management system (Progressive Agriculture, 2016)
Present study was carried out to evaluate the hatching and growth performances of guinea fowls (Numida meleagris) kept under intensive rearing system at the Bangladesh Agricultural University Poultry Farm, Mymensingh. To develop a base population of guinea fowls at BAU Poultry Farm, a good number of hatching eggs were collected from different regions of the country. In first phase, the physical features of hatching eggs, their incubation period, care and handling of eggs during incubation, their fertility and hatchability were investigated. Eggs were hatched in a home incubator incubator at BAU Poultry Farm. In second phase, brooding management of the keets, growth performances, prevention and control of diseases and mortality of the birds were observed. All the activities were performed at the Laboratory of Poultry Science and the Poultry Farm of Bangladesh Agricultural University. Brooding of keets was performed under full intensive system in a littered floor. Broiler starter feed was supplied during the brooding period. Results showed that the shape of egg was top like and both white and spotted cream color shell was found. The average egg weight was 38g per egg and shell thickness was 0.52 mm. The incubation period was 28 days. Fertility and hatchability on set eggs were 80 and 68%, respectively. Dead in shell and dead in germ were 15 and 4%, respectively. The average day-old keet weight was 25.8 g. Average feed intake per bird per day during 0-4, 5-8 and 9-11 weeks of age were 10.22, 30.91 and 52.6 g with the feed conversion ratios were 3.25, 3.05 and 2.88, respectively. The keets mortality up to 11 weeks was 10%. Economic feasibility should be taken into consideration with the observation of egg production and other associated parameters keeping guinea under complete free-range rearing system.Progressive Agriculture 27 (1): 70-77, 2016